Is fatigue related to temperament and character dimensions in patients with multiple sclerosis? - Üstün, Suzan; Sa?lam, Sadullah; Sa?lam, Sema; Kulo?lu, Murat; Bulut, Serpil (My University, 2012)
Objective: To examine the relationship between fatigue and temperament-character inventory among patients with multiple sclerosis (MS). Material and Method: This study was conducted at a tertiary referral center between August-December 2010. Overall 75 patients with MS and 75 healthy volunteers in the control group were included into study. Patients with MS and controls were divided into two groups as fatigue and non-fatigue. The personal features of patients and controls were determined using the temperament-character inventory. "Individuals with fatigue were detected using the fatigue severity scale". Results: In the study, harm avoidance and impulsiveness were high, but social scceptance was low, among the MS patients. Namely, fatigue patients with MS are more reluctant, passive, distrustful, easily fatigue, pessimistic, avoiding from harmful conditions and intolerant individuals than non-fatigue patients with MS and controls. Patients with MS have more fatigue than healthy individuals although they were not entered to the "fatigue classification" according to FSS. Persistence and purposefulness scores were low among MS patients. Namely, fatigue patients with MS are more indolent, inactive, hesitant, irregular, rarely working for high success, tend to easily renunciation, and purposeless individuals than healthy volunteers. Discussion: Fatigue significantly affects the temperament and character features in patients with multiple sclerosis.
Multipl sklerozlu hastalarda yorgunluk mizaç karakter profili ile i?lişkili mi?
Keywords: Fatigue; Multiple sclerosis; Personality; Temperament and character inventory